La translation du « vieil langaige et prose, en nouveau et rime » : Anne de Graville et les visées épidictiques du Beau romant - Bouchard, Mawy (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2012)
Around 1521, when Anne de Graville published her adaptation of Boccacio’s Teseida—which had already been translated into French in the second half of the fifteenth century—she was already known for her rendering of Alain Chartier’s Belle dame sans merci into rondeaux. Although the poetical transformation at work in this earlier piece may at first appear as an end in itself, a closer analysis of the process of poetical “translation” reveals another dimension of the text: that is, Graville’s exploration of new modes of male and female discourse. Apparently designed as a word-for-word rendition of Chartier’s dialogue, Graville’s rondeaux are marked by subtle shifts of textual perspective aimed at reinforcing the lady’s rhetorical stance. Goaded by the “translation pretext” at work in the rondeaux, I wish here to explore the rhetorical strategies deployed by Graville in the Beau Romant des deux amants, where, though posing as a humble commissioned writer, she deftly manipulates the topoi of a still dominantly masculine genre. While from the 1530s onwards the genre was to benefit from female contributions, gradually accustoming readers to the “feminization” of sentimental narratives, it still remains to be established whether the need for a feminized rendering of the genre’s discursive modes was articulated in a similar guise in the previous decade.